[Two students in Yosemite Hall dorm] (1977)
One student is sitting cross legged on the carpeted floor in front of a bureau and another sitting in an armchair with cushions in front of a single bed in the room. As it is a single room this is possibly an RA or Residence Advisor, a person who lives in the room and provides assistance to students living in the dorm rooms. One small poster and a record player provide the only decoration.